Derivatization of agelastatin A leading to bioactive analogs and a trifunctional probe. Issue 8 (15th April 2016) - Jouanneau, Morgan; McClary, Brandon; Reyes, Jeremy Chris P.; Chen, Rong; Chen, Yuling; Plunkett, William; Cheng, Xin; Milinichik, Andrew Z.; Albone, Earl F.; Liu, Jun O.; Romo, Daniel
Graphical abstract: Abstract: (−)-Agelastatin A (AglA, 1 ), a member of the pyrrole-aminoimidazole marine alkaloid (PAI) family, possesses a unique tetracyclic structure and is one of the most potent anticancer PAIs isolated to date. In efforts to expand the SAR of these agents and delineate sites that tolerate modification while retaining activity, we synthesized several derivatives and tested their anticancer activity. The cytotoxic effects of these derivatives were measured against several cancer cell lines including cervical cancer (HeLa), epidermoid carcinoma (A431), ovarian (Igrov and Ovcar3), osteosarcoma (SJSA1), acute T cell leukemia (A3), epidermoid carcinoma (A431) in addition to primary human chronic lymphocytic leukemia (CLL) cells. New positions for modification of AglA and new substitutions were explored leading to novel derivatives, 14-chloro AglA (3 ) and 14-methyl AglA (12 ), that retained activity toward various cancer cell lines with decreased toxicity toward B- and T-cells. The SAR data informed the synthesis of a trifunctional probe bearing an alkyne and a diazirine potentially useful for cellular target identification.